2001
DOI: 10.1042/bj3530503
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-induced prostacyclin production is mediated by a protein kinase C (PKC)-dependent activation of extracellular signal-regulated protein kinases 1 and 2 involving PKC-δ and by mobilization of intracellular Ca2+

Abstract: We reported previously that vascular endothelial growth factor (VEGF) stimulates prostacyclin (PGI2) production via activation of the extracellular signal-regulated kinase (ERK) cascade. In this paper, we examined the role of protein kinase C (PKC) in this pathway. VEGF-induced PGI2 generation and arachidonic acid release in human umbilical vein endothelial cells were inhibited by the PKC inhibitors GF109203X and calphostin C. VEGF increased PKC activity and immunoreactivity of the PKCδ, α and ε isoforms in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 0 publications
6
60
0
1
Order By: Relevance
“…Given that NP-1 does not have a known signaling function, we next examined other signaling pathways that could be responsible for mediating VEGF-dependent inhibition of DRG growth cone collapse. Prostaglandins exert direct effects on sensory neurons via specific EP and IP receptors (37)(38)(39)(40) and also mediate biological functions of VEGF (12,16). The role of prostanoids in regulating neurotrophic or growth cone activity has not been examined previously, however (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that NP-1 does not have a known signaling function, we next examined other signaling pathways that could be responsible for mediating VEGF-dependent inhibition of DRG growth cone collapse. Prostaglandins exert direct effects on sensory neurons via specific EP and IP receptors (37)(38)(39)(40) and also mediate biological functions of VEGF (12,16). The role of prostanoids in regulating neurotrophic or growth cone activity has not been examined previously, however (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were grown in Ham's F-12 medium containing 10% fetal bovine serum and 25 g/ml hygromycin B. PAE cells expressing either KDR (PAE/KDR) or Flt-1 (PAE/Flt-1) were provided by Professor Lena Claesson-Welsh and grown in Ham's F-12 medium containing 10% fetal bovine serum and 250 g/ml gentamicin G418. Dorsal root ganglion (DRG) explants from newborn rats were cultured as described (33, 34) on 24-well tissue culture plates precoated with poly-D-lysine (10 g/ml) and laminin (10 g/ml) in serum-free DMEM/F-12 medium supplemented with 100 g/ml transferrin, 16 g/ml putrescine, 5 g/ml insulin, 50 ng/ml thyroxine, 50 ng/ml triiodothyronine, 39 ng/ml sodium selenite, 100 g/ml crystallized bovine serum albumin, and with or without nerve growth factor (50 ng ml Ϫ1 , mouse 7 S form, Alomone Labs). Cytosine arabinofuranoside (10 M) was added after 1 day in culture to kill non-neuronal cells.…”
Section: Methodsmentioning
confidence: 99%
“…VEGF exerts its diverse biological effects in endothelial cells through high-affinity binding with two tyrosine-kinase receptors, Flt-1 (VEGFR1) and KDR (VEGFR2) (Neufeld et al, 1999;Zachary, 2003). KDR is activated through ligandstimulated receptor dimerization and trans(auto)phosphorylation of multiple tyrosine residues in the cytoplasmic domain (Dougher and Terman, 1999;Takahashi et al, 2001), triggering an array of early signalling events mediating cellular biological responses, including production of prostacyclin and nitric oxide, increased cell survival, migration, proliferation and angiogenesis (Waltenberger et al, 1994;Xia et al, 1996;Abedi and Zachary, 1997;Laitinen et al, 1997;Wheeler-Jones et al, 1997;Gerber et al, 1998;AbuGhazaleh et al, 2001;Gliki et al, 2001;Takahashi et al, 2001;Zachary, 2003). The role of gene expression in endothelial functions regulated by VEGF-A 165 is still poorly understood, but recent findings from cDNA and oligonucleotide array screening have identified the endothelial gene expression profile induced by VEGF-A 165 (Abe and Sato, 2001;Liu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of a dominantnegative ERK2 mutant blocks either JNK or ERK activity, indicating a cross-talk between ERK and JNK (72). It has been reported that VEGF-A induced activation of ERK kinase is dependent on the Ras-Raf-MEK-ERK pathway (70) or PLC-yinduced PKC-activation of Raf-MEK-ERK pathway (75)(76)(77). Two reports also suggest another novel pathway for VEGF-A-induced activation involving NO-mediated Raf-1 activation (71,95).…”
Section: Proliferationmentioning
confidence: 99%